Analysis of the association of sugammadex with the length of hospital stay in patients undergoing abdominal surgery: a retrospective study - Jing Tan; Jianhua He; Lijun Wang; Jia Fang; Pengyi Li; Zhenghuan Song; Qingming Bian (BMC Anesthesiology, 2023)
Abstract Background Sugammadex is a newer medication used for rapid and reliable reversal of neuromuscular blockade. This study evaluated whether sugammadex could reduce the length of postoperative hospital stay in patients undergoing abdominal surgery. Methods This single center retrospective cohort study included patients who underwent major abdominal surgery between January 2015 and October 2019. Patients were randomized according to reversal with sugammadex or spontaneous recovery. The primary outcome was length of postoperative hospital stay. The secondary outcomes were length of post-anesthetic care unit (PACU) stay, postoperative ambulation time, time-to-first-defecation, and incidence of pulmonary complications. After 1:1 propensity score matching, univariate and multiple linear regression analyses estimated the differences in outcomes. Results Of the 1614 patients, 517 received sugammadex and 645 spontaneously recovered. After adjusting for potential confounders, non-linear relationship was detected between administration of sugammadex and the length of postoperative hospital stay (β = 0.29 95% confidence interval CI: [− 1.13, − 0.54], P = 0.4912). However, it was associated with shorter PACU stay (β = − 20.30 95% CI: [− 24.48, − 17.11], P < 0.0001), shorter time to postoperative ambulation movement (β = − 0.43 95% CI: [− 0.62, − 0.23], P < 0.0001), and reduced time-to-first-defecation (β = − 2.25 95% CI: [− 0.45, − 0.05], P = 0.0129), when compared to the spontaneously recovered group. The incidence of pneumonia in the sugammadex group was significantly lower than that in the spontaneously recovered group (18.6% [44/237] vs. 39.2% [93/237] P < 0.05). Conclusions Neuromuscular blockade reversal with sugammadex after abdominal surgery demonstrated an excellent recovery profile and was associated with decreased risk of pneumonia, although it did not affect the length of postoperative hospital stay.